PENERAPAN METODE BERCERITA BERBASIS VARIASI MEDIA CERITA UNTUK MENINGKATKAN KEMAMPUAN MENYIMAK ANAK USIA 4-5 TAHUN - Brigita Puridawaty (Magister Scientiae, 2017)
Early childhood is the start of all children growth and rapid development, in many aspects. One of the most important development aspects is the language capacity. Language capacity is a crucial matter as it later becomes the foundation for children to develop other capacities. An important early childhood language capacity is listening comprehension. Listening comprehension can be developed through story telling method. Story telling is a pleasant and fun method to do as it facilitates the children to naturally learn in order to improve their language ability. The story telling method applies various media to grow interest for the children’s sake. It is then hoped that the young children listening comprehension is significantly developed through the various media-based story telling method.